The societal conditions for achieving sufficiency through voluntary work time reduction: Results of a pilot study in Western Switzerland - Sahakian, Marlyne; Rossier, Clémentine (Frontiers in Sustainability, 2022)
Can the voluntary reduction of working hours as a sufficiency practice promote more environmentally sustainable forms of consumption along with human well-being? In this exploratory study conducted at the end of 2018 in Western Switzerland, we use the social practices and systems of provision approaches and a definition of well-being based on human need satisfaction to answer this question in the context of an affluent country where women typically work-part-time after the arrival of children due to limited family policies. In-depth interviews with people in couples, with families, where men have also voluntarily engaged in work time reduction (WTR) (n=14), indicate that some do indeed simultaneously enjoy a high level of well-being, while limiting consumption and ecological impact. However, these are almost exclusively couples with high cultural and social capital who have adopted non-consumerist and gender egalitarian norms, despite the ‘culture of affluence’ that dominates in Swiss society. Moreover, truly resource-sufficient lifestyles seem to be possible only for people who live in settings that offer ecological options by default, thus emphasizing the importance of systems of provision that make some forms of consumption and well-being more probable and possible than others. The article therefore argues that sufficiency as a practice must go beyond personal motivations to consider the societal conditions that support sustainable well-being.